KEPATUHAN MINUM OBAT DAN KUALITAS HIDUP DI ANTARA PASIEN HIPERTENSI - Meliala, Sylvia Maria Sembiring; Widyaningsih, Tri; Angow, Tivani Sesilia; Diannita, Catharina Guinda; Manihuruk, Gracia Aktri Margaret (STIKES Suaka Insan, 2025)
Hypertension is a chronic condition that necessitates medication adherence for effective blood pressure control. Hypertensive patients who are compliant with their medication regimen often exhibit higher emotional well-being, which significantly influences their quality of life (QoL).The aim of this study was to identify the correlation between medication adherence and quality of life among hypertensive patients. This quantitative correlational study employed a cross-sectional design involving 122 respondents selected based on pre-defined inclusion and exclusion criteria. Data were collected using the MMAS-8 (Morisky Medication Adherence Scale) and the WHOQOL-BREF questionnaire. The data were then subjected to univariate and bivariate analysis using the Chi-Square test.The findings revealed a significant relationship between medication adherence and quality of life among hypertensive patients (p-value = 0.001). This significant correlation suggests that patients with higher medication adherence reported a better quality of life. It is anticipated that these results will encourage individuals with hypertension to develop greater awareness of the importance of adhering to prescribed medications as a means of improving their overall quality of life. Furthermore, this study can serve as a valuable reference for healthcare professionals in their efforts to improve patient adherence through appropriate education and scheduled consultations.